A leaf wax biomarker record of early Pleistocene hydroclimate from West Turkana, Kenya. (15th April 2018) - Lupien, R.L.; Russell, J.M.; Feibel, C.; Beck, C.; Castañeda, I.; Deino, A.; Cohen, A.S.
Abstract: Climate is thought to play a critical role in human evolution; however, this hypothesis is difficult to test due to a lack of long, high-quality paleoclimate records from key hominin fossil locales. To address this issue, we analyzed organic geochemical indicators of climate in a drill core from West Turkana, Kenya that spans ∼1.9–1.4 Ma, an interval that includes several important hominin evolutionary transitions. We analyzed the hydrogen isotopic composition of terrestrial plant waxes (δDwax ) to reconstruct orbital-timescale changes in regional hydrology and their relationship with global climate forcings and the hominin fossil record. Our data indicate little change in the long-term mean hydroclimate during this interval, in contrast to inferred changes in the level of Lake Turkana, suggesting that lake level may be responding dominantly to deltaic progradation or tectonically-driven changes in basin configuration as opposed to hydroclimate. Time-series spectral analyses of the isotopic data reveal strong precession-band (21 kyr) periodicity, indicating that regional hydroclimate was strongly affected by changes in insolation. We observe an interval of particularly high-amplitude hydrologic variation at ∼1.7 Ma, which occurs during a time of high orbital eccentricity hence large changes in processionally-driven insolation amplitude. This interval overlaps with multiple hominin species turnovers, the appearance of new stone tool technology, and hominin dispersal out of Africa, supporting the notion that climate variability played an important role in hominin evolution. Highlights: Early Pleistocene rainfall in East Africa was driven by changes in seasonal insolation. There was an interval of extreme hydrologic variability ∼1.8–1.7 Ma in West Turkana. Climate variability selects for adaptability and drives hominin evolution.